Discovery of wide low and very low-mass binary systems using Virtual Observatory tools. Issue 3 (1st December 2016) - Gálvez-Ortiz, M. C.; Solano, E.; Lodieu, N.; Aberasturi, M.
Abstract: The frequency of multiple systems and their properties are key constraints of stellar formation and evolution. Formation mechanisms of very low-mass (VLM) objects are still under considerable debate, and an accurate assessment of their multiplicity and orbital properties is essential for constraining current theoretical models. Taking advantage of the virtual observatory capabilities, we looked for comoving low and VLM binary (or multiple) systems using the Large Area Survey of the UKIDSS LAS DR10, SDSS DR9 and the 2MASS Catalogues. Other catalogues ( WISE, GLIMPSE, SuperCosmos, etc.) were used to derive the physical parameters of the systems. We report the identification of 36 low and VLM (∼M0-L0 spectral types) candidates to binary/multiple system (separations between 200 and 92 000 au), whose physical association is confirmed through common proper motion, distance and low probability of chance alignment. This new system list notably increases the previous sampling in their mass-separation parameter space (∼100). We have also found 50 low-mass objects that we can classify as ∼L0-T2 according to their photometric information. Only one of these objects presents a common proper motion high-mass companion. Although we could not constrain the age of the majority of the candidates, probably most of them are still bound except four that may be under disruption processes. We suggest that our sample could be divided in two populations: one tightly bound wide VLM systems that are expected to last more than 10 Gyr, and other formed by weak bound wide VLM systems that will dissipate within a few Gyr.